Experimental Research on Heating Transfer Improvement of Materials that Change Phase in Tunnels in Cold Regions - Xu Zhang; Dianwei Qi; Wanjiang Wang; Jiaqi Zhang; Hongchao Yan; Xiancheng Li (Geofluids)
In tunnel heating systems, phase change materials may minimize the consumption of conventional electric energy, which is very considerate in the field of tunnel heating in cold regions. Because of the phase change material’s poor heat conductivity, its annual growth rate heat absorption and release is slower; thus, the majority of phase change heat storage systems must improve heat transmission. In this study, a spiral metal ring is implanted in the paraffin to improve heat transmission to achieve this objective using a concentric sleeve-type paraffin heat storage device as a medium. Experiments were performed out in order to determine the effects of heating rate, hot fluid flow rate, and the use of a spiral metal ring on the heat storage and release process of a thermal storage device. In comparison to the paraffin thermal storage device, the embedding of the spiral metal ring accelerates the internal thermal performance of the composite heat storage device, resulting in a more uniform temperature distribution. When the thermal radiation heating rate is 60°C, 65°C, or 70°C during the heat storage process, the heat storage time of the composite heating storage device is reduced by 59.2 percent, 44.4 percent, and 40.7 percent, respectively. When the ambient temperature is 26°C and the heat storage device’s starting temperature is 65°C, the exothermic time is reduced by 22.6 percent.